Effects of Slaughter Age on Myosin Heavy Chain Isoforms, Muscle Fibers, Fatty Acids, and Meat Quality in Longissimus Thoracis Muscle of Tibetan Sheep - Bao, Gaoliang; Liu, Xiu; Wang, Jiqing; Hu, Jiang; Shi, Bingang; Li, Shaobin; Luo, Yuzhu (Frontiers in Veterinary Science, 2021)
This study investigated the effect of slaughter age on meat quality, fatty acid profile, and expression of myosin heavy chain (MyHC) isoform genes in Tibetan sheep. A total of 24 Tibetan sheep including 4-months-old (4 m), 1.5-years-old (1.5 y), 3.5-years-old (3.5 y), and 6-years-old (6 y) were randomly selected. The results indicated that the MyHC Ⅱx and MyHC Ⅱb mRNAs increased with age, whereas MyHC Ⅱa mRNA decreased. MyHC Ⅰ mRNA was highest at 3.5-years-old (3.5 y). Intramuscular fat (IMF) was highest at 1.5-years-old (1.5 y), the pH45min and pH24h value of 6-years-old (6 y) sheep were lower than the other groups, shear force of the meat increased with age (P<0.05), and drip loss increased with age (P<0.01). Tibetan sheep at 1.5 y had the lowest saturated fatty acid (SFA) contents and highest mono unsaturated fatty acid (MUFA) contents (P<0.05). These results demonstrate the effect of age on meat quality of Tibetan sheep through regulation of expression of the MyHC isoforms which changed the myofiber types, and 1.5-years-old Tibetan sheep meat was more suitable for a healthy human diet.